Translucency of Zirconia Ceramics before and after Artificial Aging. Issue 1 (11th March 2018) - Walczak, Katarzyna; Meißner, Heike; Range, Ursula; Sakkas, Andreas; Boening, Klaus; Wieckiewicz, Mieszko; Konstantinidis, Ioannis
Abstract: Purpose: The aging of zirconia ceramics (Y‐TZP) is associated with tetragonal to monoclinic phase transformation. This change in microstructure may affect the optical properties of the ceramic. This study examines the effect of aging on the translucency of different zirconia materials. Materials and Methods: 120 disc‐shaped specimens were fabricated from four zirconia materials: Cercon ht white, BruxZir Solid Zirconia, Zenostar T0, Lava Plus (n = 30 per group). Accelerated aging was performed in a steam autoclave (134°C, 0.2 MPa, 5 hours). CIELab coordinates (L*, a*, b*) and luminous reflectance (Y) were measured with a spectrophotometer before and after aging. Contrast ratio (CR) and translucency parameter (TP) were calculated from the L*, a*, b*, and Y tristimulus values. The general linear model (Bonferroni adjusted) was used to compare both parameters before and after aging, as well as between the different zirconia materials ( p ≤ 0.05). Results: CR and TP differed significantly before and after aging in all groups tested. Before aging, Zenostar T showed the highest and Lava Plus showed the lowest translucency. After aging, Cercon ht and Zenostar T showed the highest and BruxZir and Lava Plus the lowest translucency. Conclusions: Aging reduced the translucency in all specimens tested. Furthermore, translucency differed between the zirconia brands tested. Nevertheless, the differences were below the detectability threshold of the human eye. The aging process can influence the translucency and thus the esthetic outcome of zirconia restorations; however, the changes in translucency were minimal and probably undetectable by the human eye.